More optimal but less regulated dorsal and ventral visual networks in patients with major depressive disorder. (March 2019) - Chen, Hui; Liu, Kai; Zhang, Bin; Zhang, Jingyu; Xue, Xiang; Lin, Yong; Zou, Danfeng; Chen, Menglin; Kong, Youyong; Wen, Ge; Yan, Jingdong; Deng, Yanjia
Abstract: Previous studies indicate that major depressive disorder (MDD) can profoundly modify the visual cortices as well as the visuo-attentional systems of brain. However, little is known on the specific pattern of the whole-network-level abnormalities. In this study, resting-state functional magnetic resonance imaging data were collected from 159 participants, including 86 medication-free MDD patients and 73 matched healthy controls. The dorsal/ventral visual networks were defined based on our previously published brain coordinates from activation likelihood estimation analyses. The static and dynamic network properties were respectively calculated and compared between MDD and control groups. Moreover, the inter-network connectivities quantified using the multivariate distance correlation between the dorsal attention network (DAN) and the two visual networks were also analyzed. Results indicated that both of the two visual networks in MDD were found with significantly increased clustering coefficient (dorsal: p  = 0.002; ventral: p  = 0.004) and higher small-worldness (dorsal: p  = 0.001; ventral: p  = 0.002) as compared with control group. A higher mean variability of dynamic functional connectivity was found in both two networks in MDDs (dorsal: p  < 0.001; ventral: p  = 0.001). Moreover, the two visual networks in MDD group showed decreased inter-network connectivities to DAN (dorsal: p  = 0.004; ventral: p  = 0.013). Taken together, these results may support that the ventral and dorsal visual systems under the pathological effect of depression are possibly characterized by a status of increased autonomy, i.e., a more optimal, economical, and efficient intra-network organization combining with increased independency and receiving less outside regulation from attention network, thus indicating the increased functional role of the brain visual systems in MDD. Highlights: 240-volume rs-fMRI are collected from 86 medication-free MDDs and 73 controls. Ventral and dorsal visual networks show more optimized organization in MDD. Higher dynamic FC variability is found in both dorsal & ventral visual networks. Ventral and dorsal visual networks show inter-network dysconnectivities to DAN in MDD.